Especial Features of Immune Answer of Mice, Immunized by Different Types of Live Influenza Vaccines Candidate on Infection, Caused by Virulent Influenza Strain - S. . Markushin; W. . Kost; A. . Rtischev; I. . Akopova; I. . Koptyeva; K. . Lisovskaya (Эпидемиология и вакцинопрофилактика)
Relevance. Live influenza vaccines are highly effective and currently used in the Russian Federation and the United States. Goal. To investigate especial features of immune response of mice, immunized by different types of live influenza vaccines and infected later by virulent influenza strain. Materials and methods. Mice were immunized by two types of live influenza vaccines candidate: cold-adapted (CA) reassortant, which inherited the 6 «internal» genes from the CA donor A/Krasnodar/101/35/59 (H2N2) and 2 genes encoding the surface proteins HA and NA from the virulent strain A/WSN/33 (H1N1) and site-specific mutants on the basis of A/WSN/33 strain, in the genome of which has been included mutations from genes of CA strains of influenza virus, encoding proteins of the polymerase complex. Immunized mice were then infected by a virulent A/WSN/33 strain of influenza virus. Results. It was shown that CA reassortant RKr35/WSN/33 and site-specific mutants Tr. № 5 and № 8 in contrast to the virulent A/WSN/33 strain were characterized by pronounced ts-phenotype and att-phenotype. Both types of live vaccines after two-time intranasal immunization induced in mice a relatively low level of humoral antibodies (log2 4,5 ± 1,2 - log2 6,0 ± 0,7). Despite the low level of induction of humoral response both types of live vaccines had similar marked protective efficiency. However, animals immunized with CA reassortant was characterized by a significant weight loss after infection with a virulent influenza strain (25%), while the infection of animals, immunized with site-specific mutants, by a similar dose of virulent flu strain has very little impact on their weight characteristics (8 - 13%). Conclusion. The data obtained indicate that antibodies to surface proteins of the virion, induced in the process of immunization, slightly inhibited the initial replication of the virulent strain and suggest that these differences in the symptoms of the infection depend on the characteristics of activated T-cell immunity. This circumstance could have a significant impact on metabolic processes in organism of infected animals.